One-year mortality and causes of death after stereotactic radiation therapy for refractory ventricular arrhythmias: A systematic review and pooled analysis - Benali, Karim; Zei, Paul C; Lloyd, Michael; Kautzner, Josef; Guenancia, Charles; Ninni, Sandro; Rigal, Louis; Simon, Antoine; Bellec, Julien; Vlachos, Konstantinos; Sacher, Frederic; Hammache, Nefissa; et al. (Trends in cardiovascular medicine, 2024)
Patients treated with cardiac stereotactic body radiation therapy (radioablation) for refractory ventricular arrhythmias are patients with advanced structural heart disease and significant comorbidities. However, data regarding 1-year mortality after the procedure are scarce. This systematic review and pooled analysis aimed at determining 1-year mortality after cardiac radioablation for refractory ventricular arrhythmias and investigating leading causes of death in this population. MEDLINE/EMBASE databases were searched up to January 2023 for studies including patients undergoing cardiac radioablation for the treatment of refractory ventricular arrhythmias. Quality of included trials was assessed using the NIH Tool for Case Series Studies (PROSPERO CRD42022379713). A total of 1,151 references were retrieved and evaluated for relevance. Data were extracted from 16 studies, with a total of 157 patients undergoing cardiac radioablation for refractory ventricular arrhythmias. Pooled 1-year mortality was 32 % (95 %CI: 23-41), with almost half of the deaths occurring within three months after treatment. Among the 157 patients, 46 died within the year following cardiac radioablation. Worsening heart failure appeared to be the leading cause of death (52 %), although non-cardiac mortality remained substantial (41 %) in this population. Age≥70yo was associated with a significantly higher 12-month all-cause mortality (p<0.022). Neither target volume size nor radiotherapy device appeared to be associated with 1-year mortality (p = 0.465 and p = 0.199, respectively). About one-third of patients undergoing cardiac stereotactic body radiation therapy for refractory ventricular arrhythmias die within the first year after the procedure. Worsening heart failure appears to be the leading cause of death in this population.
Keywords: senioři; Death; Disease Progression; senioři nad 80 let; srdeční arytmie; Radiotherapy; Ventricular tachycardia; progrese nemoci; Time Factors; výsledek terapie; Risk Assessment; Middle Aged; mužské pohlaví; příčina smrti; Arrhythmia; Adult; Arrhythmias, Cardiac; Radiosurgery; Heart failure; Aged, 80 and over; Radioablation; ženské pohlaví; hodnocení rizik; Radiation therapy; Humans; Mortality; časové faktory; srdeční selhání; lidé středního věku; rizikové faktory; Refractory; dospělí; Female; Aged; Risk Factors; Treatment Outcome; radiochirurgie; Cause of Death; Heart Failure; lidé; Male